The Effect of Extensive Reading on Students Reading Comprehension - Dadan Hidayat; Titi Dewi Rohati (LPPM Universitas Bina Sarana Informatika, 2020)
This research investigated the effect of extensive reading on students reading comprehension. The writer used the quantitative as the researched method and the writer used the queasy experiment as the research design. For collecting the data the writer gave the test for experimental and control group. For experimental group the writer used the extensive reading method as the reading class room and the other method for the control group. After the post- test gave to both classes, the writer analyzed it by using SPPS 20 program to found out the improvement on student reading comprehension after extensive reading implied on reading classroom. Based on the finding and discussion. It can be concluded that hypothesis was accepted. It meant that there was effect on extensive reading on student reading comprehension. Based on the resulted of this research. The writer suggested the teacher to used extensive reading on reading process to improved student reading comprehension.